Pengaruh Corporate Social Responsibility dan Good Corporate Governance Terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Kimia yang Terdaftar Di Bursa Efek Indonesia - Muhammad Basri (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2020)
This study aims to analyze and determine the effect of Corporate Social Responsibility and Good Corporate Governance on the value of the Chemical Sub-sector companies listed on the Indonesia Stock Exchange (IDX). Good Corporate Governance in this study is measured by looking at the independence of the board of commissioners and institutional ownership. This research uses the associative approach method. The population used in this study were 10 Sub-Sector Chemical companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018. While the sample taken as many as 6 companies using purposive sampling To obtain the data needed in this study, the data analysis technique in this study used multiple linear regression, which previously tested the classical assumption. The results of this study partially show that corporate social responsibility has a significant effect on firm value. Independent board of commissioners has an effect on firm value. institutional ownership has an effect on firm value. Simultaneously, corporate social responsibility, independent board of commissioners and institutional ownership have a joint effect on company value